Sustainable power generation fiber material based on moisture absorption-evaporation circulation and preparation method thereof

The asymmetric fiber structure with moisture absorption and discharge capabilities, combined with redox reactions, addresses the limitations of hydrovoltaic power generation, providing a stable high-current output for wearable and environmental applications.

CN119189453APending Publication Date: 2024-12-27SHENHUA SHENDONG COAL GRP +3

Patent Information

Application Number
CN202411591197.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Current hydrovoltaic power generation technologies face limitations such as low ion concentration, unstable electrical signal maintenance, uncontrollable hygroscopicity, low flexibility, and mechanical issues, leading to unsustainable output and limited versatility and portability.

Method used

A sustainable power generation fiber material with an asymmetric structure that absorbs moisture on one side and discharges it on the other, utilizing capillary effects and micro-nano channels for continuous water flow, combined with metal electrodes for redox reactions to enhance ion current density and output.

Benefits of technology

The material achieves a stable high-performance output of over 12.5V, ensuring continuous power generation through directional ion migration and redox reactions, suitable for wearable devices and environmental monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119189453A_ABST
    Figure CN119189453A_ABST
Patent Text Reader

Abstract

The invention provides a sustainable power generation fiber material based on moisture absorption-evaporation circulation and a preparation method thereof. The method comprises the following steps: S1, preparing a moisture absorption layer; s2, preparing a nanofiber moisture removal layer through an electrostatic spinning technology; s3, preparing an evaporation layer; and S4, the active metal electrode is installed on the moisture absorption layer, the graphite electrode is installed on the evaporation layer, and the sustainable power generation fiber material based on moisture absorption-evaporation circulation is integrated. According to the material prepared by the invention, the three-layer asymmetric fiber structure design of'moisture absorption-moisture removal-evaporation 'and gradually increased electronegativity are utilized, the functions of moisture absorption, sweat releasing and water photovoltaic power generation are realized at the same time, voltage output exceeding 12.5 V can be provided, the material is combined with masks, clothes and the like, the wearing comfort can be met, an energy collection system can be constructed, and the material is suitable for popularization and application. Direct power supply for commercial electronic equipment is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power generation fiber materials, and in particular to a sustainable power generation fiber material based on a moisture absorption-evaporation cycle and a preparation method thereof. Background Art

[0002] Water, which is ubiquitous in nature, stores 35% of all solar energy on Earth, resulting in a huge energy conversion in the water cycle. In recent years, hydropower generation technology, especially water evaporation power generation (WEG) and wet electricity generation (MEG), has attracted widespread attention due to its spontaneous DC output. WEG converts atmospheric heat energy into electrical energy through the evaporation of water, and its electrical signal comes from the charge separation of liquid water in charged nanomaterials. Limited by the charge separation efficiency and the low ion concentration in water, the current output of WEG is low (mostly less than 1μA / cm 2 ). Since the electrical signal output of WEG relies on a stable supply of liquid water in its application, its versatility and portability are limited.

[0003] MEG technology is designed to capture the energy generated by the change in chemical potential energy when water molecules change from a gaseous state in the air to an absorbed state in a functional material. The electrical signal is generated by the direct migration of ions in highly hydrophilic materials such as ionomers. Due to the disappearance of the ion concentration gradient after water saturation, the generated electrical signal is difficult to maintain for a long time (mainly a few seconds or hours, rarely a few days). In addition, the practical application of this material is hindered by problems such as uncontrollable hygroscopicity, low flexibility and mechanical properties.

[0004] Fabrics can serve as ideal carriers for hydrophotovoltaic technology. First, fabrics are widely used in all aspects of our lives, and soft, lightweight, and sustainable energy-harvesting fabrics (such as triboelectricity, thermoelectricity, etc.) are considered to have great application prospects. Second, fabrics can be easily designed with controllable moisture transport structures, which is conducive to the application of hydrophotovoltaic power generation. In addition, the series-parallel connection of multiple devices is a way to promote the practical application of hydropower generation. Fabrics can be simply sewn or disassembled, providing a convenient and practical integration method. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a sustainable power generation fiber material based on a moisture absorption-evaporation cycle and a preparation method thereof in view of the deficiencies in the prior art. The sustainable power generation fiber material has an asymmetric fiber structure, which can absorb moisture on one side by utilizing the capillary effect and effectively discharge moisture from the other side. Moisture absorption-evaporation ensures a continuous flow of water through the negatively charged micro-nano channels in the fiber membrane, thereby solving the problem of unsustainable output in hydrovoltaic power generation. The flow of water also drives the metal electrodes to undergo redox reactions to produce a large number of ions. The directional movement of these ions increases the ion current density, thereby producing sustainable high-performance output. This power generation fiber material combined with masks, clothes, etc. can not only meet the wearing comfort, but also construct an energy collection system to directly power commercial electronic devices.

[0006] The method comprises the following steps:

[0007] Step S1, preparing a hygroscopic layer: dissolving cellulose acetate in an organic solvent, preparing a cellulose microfiber membrane by electrospinning technology, then dissolving a hygroscopic salt in deionized water, soaking the cellulose microfiber membrane in the hygroscopic salt solution, placing it in a microwave reactor to in-situ grow hygroscopic salt ions, and preparing a hygroscopic layer after drying;

[0008] Step S2, preparing a moisture-dissipating layer: dissolving polyacrylonitrile and a thermally conductive filler in an organic solvent, using the moisture-absorbing layer as a receiving substrate, and preparing a nanofiber moisture-dissipating layer by electrospinning technology;

[0009] Step S3, preparing an evaporation layer: dissolving polyvinylidene fluoride and a layered filler in an organic solvent, and uniformly depositing nanofibers on the moisture removal layer by electrospinning technology to prepare an evaporation layer;

[0010] Step S4, integration of power generation fiber materials: installing the active metal electrode on the hygroscopic layer, installing the graphite electrode on the evaporation layer, and integrating sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

[0011] In step S1, the organic solvent for dissolving cellulose acetate is at least one of acetone, dimethylformamide, and glacial acetic acid, and the concentration of cellulose in the solution is 0.2-30 wt%.

[0012] In step S1, when the cellulose micron fiber membrane is prepared by electrospinning technology, the electrospinning voltage is 15-45 kV, the spinning solution consumption rate is 0.5-12 mL / h, the receiving distance is 10-30 cm, and the average diameter of the obtained cellulose micron fiber is 0.5-6 μm, and the fiber membrane thickness is 5-200 μm.

[0013] In step S1, the hygroscopic salt is at least one of lithium chloride, calcium chloride, sodium chloride and potassium nitrate, the concentration of the hygroscopic salt in deionized water is 0.5-50wt%, the output power of the microwave reactor is 200-2000W, the reaction temperature is 30-100°C, and the reaction time is 1-60min.

[0014] The hygroscopic layer designed by the present invention is composed of hygroscopic salt ions and hydrophilic cellulose micron fiber membrane, which has high hygroscopicity and provides positive and negative ions, thereby increasing the ion current density during directional water transport.

[0015] In step S2, the organic solvent is at least one of dimethylformamide, dimethyl sulfoxide, sulfolane, and ethylene nitrate, and the concentration of polyacrylonitrile in the organic solvent is 0.2 to 30 wt %;

[0016] The thermal conductive filler is at least one of aluminum oxide, zinc oxide, aluminum nitride, boron nitride, graphene, carbon nanotubes, silicon carbide, and silicon dioxide, and the concentration of the thermal conductive nano filler in the organic solvent is 0.5-50wt%.

[0017] In step S2, when the nanofiber dehumidification layer is prepared by electrospinning technology, the electrospinning voltage is 15-45 kV, the spinning solution consumption rate is 0.2-8 mL / h, the receiving distance is 10-30 cm, the average diameter of the obtained nanofibers is 50-800 nm, and the thickness of the dehumidification layer fiber membrane is 5-200 μm.

[0018] The moisture removal layer designed in the present invention is composed of thermally conductive fillers and polyacrylonitrile nanofiber membranes. The hydrophilicity of polyacrylonitrile can effectively absorb water molecules from the moisture absorption layer. The thermally conductive fillers provide a good thermal conduction path, which can effectively transfer heat to the evaporation layer and increase the water evaporation rate.

[0019] In step S3, the organic solvent is at least one of dimethylformamide, methyl vinyl ketone and dichloromethane, and the concentration of polyvinylidene fluoride in the organic solvent is 0.2-30 wt %;

[0020] The layered filler is at least one of nano-mica flakes, natural montmorillonite, boron nitride and talcum powder, and the concentration of the layered filler in the organic solvent is 0.5-50wt%.

[0021] In step S3, in the process of uniformly depositing the nanofibers on the dehumidification layer by electrospinning technology, the electrospinning voltage is 15-45 kV, the spinning solution consumption rate is 0.1-5 mL / h, the receiving distance is 10-30 cm, the average diameter of the obtained nanofibers is 10-600 nm, and the thickness of the evaporation layer fiber membrane is 5-200 μm.

[0022] The evaporation layer designed in the present invention is composed of a layered filler and a polyvinylidene fluoride nanofiber membrane. The hydrophobicity of polyvinylidene fluoride can form an asymmetric wetting structure with the moisture-removing layer, effectively promoting the directional transport of water. The layered filler provides strength and barrier properties, thereby improving multiple mechanical and thermodynamic properties of the fiber membrane, including tensile strength, puncture resistance, heat deformation temperature, etc.

[0023] In step S4, the active metal electrode is at least one of aluminum, copper, iron, and silver, and the active metal electrode undergoes a redox reaction to provide a stable ion supply.

[0024] The present invention also provides a sustainable power generation fiber material based on moisture absorption-evaporation cycle, which is prepared by the method described.

[0025] The sustainable power generation fiber material based on the moisture absorption-evaporation cycle can be applied to low-power environmental monitoring equipment, wearable electronic devices, smart textiles, remote sensors, and medical health monitoring. In environmental monitoring equipment, the material can achieve continuous power generation through changes in air humidity, providing a stable energy supply for sensors, and is particularly suitable for environmental monitoring in the wild or remote areas; in wearable devices and smart textiles, the material can generate electricity using human sweat or changes in surrounding humidity to provide power for small electronic components, and achieve continuous energy supply for mobile health monitoring or smart clothing; at the same time, this fiber material can also be used in medical health monitoring equipment, powering the equipment through a moisture absorption-evaporation cycle, reducing dependence on external power sources, and improving portability and sustainability.

[0026] Beneficial effects: The sustainable power generation fiber material based on the moisture absorption-evaporation cycle and the preparation method thereof provided by the present invention have a single moisture conductivity due to the asymmetric structural design in the vertical direction. Because of the Laplace pressure difference, the liquid will diffuse autonomously, and the multilayer structure shows the characteristics of enhanced hydrophobicity and reduced pore size, which ensures the directional transport of water inside the fiber membrane. The gradually increasing electronegative material promotes charge separation and directional migration of ions, thereby generating a stable high current output for a long time, and the redox reaction liquid of the active metal electrode can provide a stable ion supply. The heat conduction path formed by the thermally conductive filler can transfer heat to the evaporation layer, promote the absorption-evaporation process of water, and ensure continuous water flow through the negatively charged micro-nano channels in the fiber membrane, thereby solving the problem of unsustainable output in hydrovoltaic power generation. A sustainable power generation fiber material based on the moisture absorption-evaporation cycle designed by the invention can provide a voltage output of more than 12.5V. This power generation fiber material combined with masks, clothes, etc. can not only meet the wearing comfort, but also construct an energy collection system to realize direct power supply for commercial electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0028] Figure 1 It is a flow chart of the method of the present invention.

[0029] Figure 2 is a scanning electron microscope image of the cellulose microfibers in Example 1.

[0030] Figure 3 is a scanning electron microscope image of the nanofibers in the moisture-wicking layer in Example 1.

[0031] Figure 4 It is the one-way water transport performance test rating report in Example 1. DETAILED DESCRIPTION

[0032] Example 1

[0033] like Figure 1 As shown, this embodiment provides a method for preparing a sustainable power generation fiber material based on a moisture absorption-evaporation cycle, comprising the following steps:

[0034] S11. Preparation of hygroscopic layer: 15wt% cellulose acetate was dissolved in dimethylformamide, and cellulose micron fiber membrane was prepared by electrospinning technology (voltage 25kV, solution consumption rate 5mL / h, receiving distance 20cm), the average diameter of the obtained fiber was 2.5μm, and the thickness of the fiber membrane was 50μm, then 20wt% lithium chloride was dissolved in deionized water, the cellulose micron fiber membrane was immersed in lithium chloride aqueous solution, and placed in a microwave reactor (output power 800W, reaction temperature 50℃, reaction time 10min) to in-situ grow lithium ions and chloride ions, and the hygroscopic layer was prepared after drying;

[0035] S12. Preparation of moisture-dissipating layer: 10 wt% polyacrylonitrile and 10 wt% silica were dissolved in dimethylformamide, and the moisture-absorbing layer was used as the receiving substrate. The nanofiber moisture-dissipating layer was prepared by electrospinning technology (voltage 25 kV, solution consumption rate 2 mL / h, receiving distance 20 cm). The average diameter of the obtained nanofibers was 400 nm, and the thickness of the moisture-dissipating layer fiber membrane was 50 μm;

[0036] S13. Preparation of evaporation layer: 10wt% polyvinylidene fluoride and 10wt% nano-mica flakes were dissolved in dimethylformamide, and the nanofibers were uniformly deposited on the dehumidification layer by electrospinning technology (voltage 25kV, solution consumption rate 1mL / h, receiving distance 20cm) to prepare the evaporation layer. The average diameter of the obtained nanofibers was 200nm, and the thickness of the evaporation layer fiber film was 50μm;

[0037] S14. Integration of power generation fiber materials: Install the aluminum electrode on the hygroscopic layer and the graphite electrode on the evaporation layer to integrate sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

[0038] Example 2

[0039] This embodiment provides a method for preparing a sustainable power generation fiber material based on a moisture absorption-evaporation cycle, comprising the following steps:

[0040] S21. Preparation of hygroscopic layer: 20wt% cellulose acetate was dissolved in acetone, and a cellulose microfiber membrane was prepared by electrospinning technology (voltage 20kV, solution consumption rate 3mL / h, receiving distance 15cm), the average diameter of the obtained fiber was 3μm, and the thickness of the fiber membrane was 100μm, then 10wt% lithium chloride was dissolved in deionized water, the cellulose microfiber membrane was soaked in the lithium chloride aqueous solution, and placed in a microwave reactor (output power 800W, reaction temperature 40°C, reaction time 15min) to in-situ grow lithium ions and chloride ions, and the hygroscopic layer was prepared after drying;

[0041] S22. Preparation of moisture-dissipating layer: 15wt% polyacrylonitrile and 5wt% graphene were dissolved in dimethylformamide, and the moisture-absorbing layer was used as the receiving substrate. The nanofiber moisture-dissipating layer was prepared by electrospinning technology (voltage 20kV, solution consumption rate 3mL / h, receiving distance 15cm). The average diameter of the obtained nanofibers was 600nm, and the thickness of the moisture-dissipating layer fiber membrane was 40μm;

[0042] S23. Preparation of evaporation layer: 15wt% polyvinylidene fluoride and 5wt% natural montmorillonite were dissolved in dichloromethane, and the nanofibers were uniformly deposited on the dehumidification layer by electrospinning technology (voltage 25kV, solution consumption rate 1mL / h, receiving distance 20cm) to prepare the evaporation layer. The average diameter of the obtained nanofibers was 400nm, and the thickness of the evaporation layer fiber film was 10μm;

[0043] S24. Integration of power generation fiber materials: Install the copper electrode on the hygroscopic layer and the graphite electrode on the evaporation layer to integrate sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

[0044] Example 3

[0045] This embodiment provides a method for preparing a sustainable power generation fiber material based on a moisture absorption-evaporation cycle, comprising the following steps:

[0046] S31. Preparation of a hygroscopic layer: 10 wt% cellulose acetate was dissolved in glacial acetic acid, and a cellulose microfiber membrane was prepared by electrospinning technology (voltage 30 kV, solution consumption rate 2 mL / h, receiving distance 20 cm), the average diameter of the obtained fiber was 1 μm, and the thickness of the fiber membrane was 20 μm, then 10 wt% calcium chloride was dissolved in deionized water, the cellulose microfiber membrane was soaked in a lithium chloride aqueous solution, and placed in a microwave reactor (output power 800 W, reaction temperature 30 ° C, reaction time 20 min) to in situ grow calcium ions and chloride ions, and the hygroscopic layer was prepared after drying;

[0047] S32. Preparation of moisture-dissipating layer: 10 wt% polyacrylonitrile and 3 wt% boron nitride were dissolved in dimethyl sulfoxide, and the moisture-absorbing layer was used as the receiving substrate. The nanofiber moisture-dissipating layer was prepared by electrospinning technology (voltage 25 kV, solution consumption rate 1 mL / h, receiving distance 20 cm). The average diameter of the obtained nanofibers was 300 nm, and the thickness of the moisture-dissipating layer fiber membrane was 100 μm;

[0048] S33. Preparation of evaporation layer: 15wt% polyvinylidene fluoride and 3wt% natural montmorillonite were dissolved in methyl vinyl ketone, and the nanofibers were uniformly deposited on the dehumidification layer by electrospinning technology (voltage 25kV, solution consumption rate 2mL / h, receiving distance 20cm) to prepare the evaporation layer. The average diameter of the obtained nanofibers was 500nm, and the thickness of the evaporation layer fiber film was 50μm;

[0049] S34. Integration of power generation fiber materials: Install the iron electrode on the hygroscopic layer and the graphite electrode on the evaporation layer to integrate sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

[0050] Example 4

[0051] This embodiment provides a method for preparing a sustainable power generation fiber material based on a moisture absorption-evaporation cycle, comprising the following steps:

[0052] S41. Preparation of a hygroscopic layer: 20 wt% cellulose acetate was dissolved in glacial acetic acid, and a cellulose microfiber membrane was prepared by electrospinning technology (voltage 15 kV, solution consumption rate 4 mL / h, receiving distance 20 cm), the average diameter of the obtained fiber was 5 μm, and the thickness of the fiber membrane was 80 μm, then 1 wt% calcium chloride was dissolved in deionized water, the cellulose microfiber membrane was soaked in a lithium chloride aqueous solution, and placed in a microwave reactor (output power 800 W, reaction temperature 30 ° C, reaction time 5 min) to in situ grow calcium ions and chloride ions, and the hygroscopic layer was prepared after drying;

[0053] S42. Preparation of moisture-dissipating layer: 10 wt % polyacrylonitrile and 1 wt % boron nitride were dissolved in dimethyl sulfoxide, and the moisture-absorbing layer was used as the receiving substrate. The nanofiber moisture-dissipating layer was prepared by electrospinning technology (voltage 15 kV, solution consumption rate 2 mL / h, receiving distance 20 cm), and the average diameter of the obtained nanofibers was 400 nm, and the thickness of the moisture-dissipating layer fiber membrane was 20 μm;

[0054] S43. Preparation of evaporation layer: 10wt% polyvinylidene fluoride and 1wt% natural montmorillonite were dissolved in methyl vinyl ketone, and the nanofibers were uniformly deposited on the dehumidification layer by electrospinning technology (voltage 15kV, solution consumption rate 1mL / h, receiving distance 20cm) to prepare the evaporation layer. The average diameter of the obtained nanofibers was 300nm, and the thickness of the evaporation layer fiber film was 20μm;

[0055] S44. Integration of power generation fiber materials: Install the silver electrode on the hygroscopic layer and the graphite electrode on the evaporation layer to integrate sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

[0056] Comparative Example 1 (hygroscopic layer is not soaked in hygroscopic salt solution)

[0057] The sustainable power generation fiber material was prepared basically by the method of Example 1. The difference is that the hygroscopic layer of this example is not soaked in a hygroscopic salt solution, but the cellulose micron fiber membrane prepared by electrospinning is directly used as the hygroscopic layer. Specifically, 15wt% cellulose acetate was dissolved in dimethylformamide, and a cellulose micron fiber membrane was prepared as a hygroscopic layer by electrospinning technology (voltage 25kV, solution consumption rate 5mL / h, receiving distance 20cm). The average diameter of the obtained fiber was 2.5μm, and the thickness of the fiber membrane was 50μm. 10wt% polyacrylonitrile and 10wt% silica were dissolved in dimethylformamide, and the hygroscopic layer was used as the receiving substrate. The nanofiber dehumidification layer was prepared by electrospinning technology (voltage 25kV, solution consumption rate 2mL / h, receiving distance 20cm). The average diameter of the nanofibers is 400nm, and the thickness of the fiber membrane of the moisture-wicking layer is 50μm; 10wt% polyvinylidene fluoride and 10wt% nano-mica sheets are dissolved in dimethylformamide, and the nanofibers are evenly deposited on the moisture-wicking layer by electrospinning technology (voltage 25kV, solution consumption rate 1mL / h, receiving distance 20cm) to prepare an evaporation layer. The average diameter of the obtained nanofibers is 200nm, and the thickness of the fiber membrane of the evaporation layer is 50μm; an aluminum electrode is installed on the moisture absorption layer, and a graphite electrode is installed on the evaporation layer to integrate a sustainable power generation fiber material based on a moisture absorption-evaporation cycle.

[0058] Comparative Example 2 (no thermal conductive filler added to the moisture removal layer)

[0059] The sustainable power generation fiber material was prepared basically by the method of Example 2. The difference is that in this example, no thermal conductive filler was added to the moisture-wicking layer. Specifically, 20wt% cellulose acetate was dissolved in acetone, and a cellulose micron fiber membrane was prepared by electrospinning technology (voltage 20kV, solution consumption rate 3mL / h, receiving distance 15cm). The average diameter of the obtained fiber was 3μm, and the thickness of the fiber membrane was 100μm. Then 10wt% lithium chloride was dissolved in deionized water, and the cellulose micron fiber membrane was immersed in the lithium chloride aqueous solution and placed in a microwave reactor (output power 800W, reaction temperature 40°C, reaction time 15min) to in-situ grow lithium ions and chloride ions, and a moisture-absorbing layer was prepared after drying; 15wt% polyacrylonitrile was dissolved in dimethylformamide, and the moisture-absorbing layer was used as the receiving substrate, and electrospinning technology (voltage 20kV, solution consumption rate 3mL / h, receiving distance 15cm) was used to prepare the moisture-absorbing layer. 20kV, solution consumption rate 3mL / h, receiving distance 15cm) was used to prepare a nanofiber dehumidification layer, the average diameter of the obtained nanofibers was 600nm, and the thickness of the fiber membrane of the dehumidification layer was 40μm; 15wt% polyvinylidene fluoride and 5wt% natural montmorillonite were dissolved in dichloromethane, and the nanofibers were evenly deposited on the dehumidification layer by electrospinning technology (voltage 25kV, solution consumption rate 1mL / h, receiving distance 20cm) to prepare an evaporation layer, the average diameter of the obtained nanofibers was 400nm, and the thickness of the fiber membrane of the evaporation layer was 10μm; a copper electrode was installed in the desiccant layer, and a graphite electrode was installed in the evaporation layer to integrate a sustainable power generation fiber material based on a moisture absorption-evaporation cycle.

[0060] Comparative Example 3 (Moisture-absorbing layer with graphite electrode)

[0061] The sustainable power generation fiber material is prepared basically by the method of Example 3, except that the hygroscopic layer in this example is installed with a graphite electrode instead of an active metal electrode. Specifically, 10wt% cellulose acetate is dissolved in glacial acetic acid, and a cellulose micron fiber membrane is prepared by electrospinning technology (voltage 30kV, solution consumption rate 2mL / h, receiving distance 20cm). The average diameter of the obtained fiber is 1μm, and the thickness of the fiber membrane is 20μm. Then 10wt% calcium chloride is dissolved in deionized water, and the cellulose micron fiber membrane is soaked in a lithium chloride aqueous solution and placed in a microwave reactor (output power 800W, reaction temperature 30°C, reaction time 20min) to in-situ grow calcium ions and chloride ions, and a hygroscopic layer is prepared after drying. 10wt% polyacrylonitrile and 3wt% boron nitride are dissolved in dimethyl sulfoxide, and the hygroscopic layer is used as the receiving substrate. By electrospinning The nanofiber dehumidification layer was prepared by electrospinning technology (voltage 25kV, solution consumption rate 1mL / h, receiving distance 20cm), and the average diameter of the obtained nanofibers was 300nm, and the thickness of the fiber membrane of the dehumidification layer was 100μm; 15wt% polyvinylidene fluoride and 3wt% natural montmorillonite were dissolved in methyl vinyl ketone, and the nanofibers were evenly deposited on the dehumidification layer by electrospinning technology (voltage 25kV, solution consumption rate 2mL / h, receiving distance 20cm) to prepare the evaporation layer, and the average diameter of the obtained nanofibers was 500nm, and the thickness of the fiber membrane of the evaporation layer was 50μm; graphite electrodes were installed in the hygroscopic layer and the evaporation layer to integrate sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

[0062] Structural characterization and performance testing:

[0063] Microscopic characterization: Scanning electron microscopy (SEM, SU8220, Hitachi, Japan) was used to observe the microstructure of each layer of fibers.

[0064] Water contact angle test: The water contact angle of each layer of fiber membrane was tested using a contact angle meter (WCA, DSA100, KRUSS, Germany).

[0065] Air permeability test: The air permeability of the material was tested using a fully automatic air permeability meter (YG461E-III, Changzhou Second Textile Instrument Factory).

[0066] One-way water transport performance test: The one-way water transport capacity of the material was tested using a liquid moisture tester (NF290, Changzhou Second Textile Instrument Factory).

[0067] Water evaporation rate and permeability test: The water evaporation rate and permeability of the material were tested using a computerized fabric moisture permeability tester (YG601H-II, Changzhou Second Textile Instrument Factory).

[0068] Electrical output performance test: The electrical output performance of the material was measured using an electrometer (Keithley 6514, Tektronix, USA).

[0069] Tensile property test: The obtained nanofiber membrane was cut to obtain tensile specimens, and the tensile properties of the composite membrane were tested using a universal tensile machine (model 4403, sensor 100N) of Instron Company of the United States according to the plastic tensile property test standard ASTM D638-2003 of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.

[0070] Experimental results: The cellulose fibers in the moisture-absorbing layer of Example 1 are evenly distributed (e.g. Figure 2 The average diameter is 2.5 μm, with a large pore size distribution; the polyacrylonitrile fiber of the moisture-wicking layer exhibits nano-protrusions due to the loading of silica (as shown in FIG. Figure 3 The average diameter is 400nm, with a small pore size distribution. This gradient fiber structure design ensures the directional transport of moisture from the moisture absorption layer to the moisture discharge layer inside the fiber membrane. Figure 4 This is a rating report generated by the liquid moisture tester according to the national standard "GB / T 21655.2-2019" to evaluate the unidirectional water transport capacity of the material. The results show that the unidirectional transfer index of the power-generating fiber material prepared in Example 1 is as high as 317.4, and its moisture absorption and quick-drying properties and moisture absorption and perspiration discharge properties both meet the standard requirements.

[0071] Table 1 compares the air permeability, unidirectional water transport performance, water evaporation rate, water permeability, electrical output performance and mechanical performance test results of the power generation fiber materials obtained in the examples and comparative examples. The examples and comparative examples all have good air permeability (157.2-220.7 mm / s), which is due to the "micron-nano" multi-scale structural design of the three-layer fiber membrane. The rich pore structure is conducive to the passage of air molecules through the fiber. Except for comparative example 1, the unidirectional transfer indexes of other examples and comparative examples are all above 142.6, and have good unidirectional water transport capacity. This is because, in addition to the gradient fiber structure design, the hygroscopic salt grown in situ in the hygroscopic layer plays a key role, while the hygroscopic layer of comparative example 1 lacks hygroscopic salts and does not have sufficient absorption for water molecules in the air, resulting in only a small amount of water molecules being transmitted to the evaporation layer. Therefore, the unidirectional transfer index is low, which also affects the water permeability. Other examples 1 to 4 and comparative examples 1 and 3 all have high water evaporation rates, while the water evaporation rate of comparative example 2 is only 42.6 g / h / m 2 This is because the moisture-dissipating layer of Comparative Example 2 lacks thermally conductive fillers and cannot form a good thermal conductive path, resulting in the inability to effectively transfer heat to the evaporation layer, thereby reducing the water evaporation rate.

[0072] Table 1

[0073]

[0074] Examples 1 to 4 and Comparative Example 2 all have a high voltage output capability (8.7V to 12.5V), because (1) the multilayer structure exhibits the characteristics of enhanced hydrophobicity and reduced pore size, which ensures the directional transport of water inside the fiber membrane; (2) the gradually increasing electronegative materials promote charge separation and directional migration of ions, thereby generating a stable high current output over a long period of time; ③ the hygroscopic salt solution soaked in the hygroscopic layer provides a large number of positive and negative ions, which increases the ion current density during directional water transport; ④ the redox reaction of the active metal electrode can provide a stable ion supply. The lower output voltage of Comparative Example 1 is because the hygroscopic layer lacks a large number of positive and negative ions provided by the salt solution, and the current density is low during directional water transport; while the hygroscopic layer of Comparative Example 3 is installed with a graphite electrode instead of an active metal electrode, and the flow of water cannot drive the graphite electrode to undergo a redox reaction to produce a large number of ions, so the output voltage is also low. The examples and comparative examples all have relatively high breaking strength (18.2-29.8 MPa), which is due to the layered filler added to the evaporation layer, which provides sufficient strength and barrier properties for the fiber material, ensuring practical applicability in outdoor environments or harsh environments.

[0075] This shows that the fiber material proposed in this embodiment can simultaneously achieve the functions of moisture absorption and perspiration removal and hydrovoltaic power generation, and has high air permeability, excellent directional water transport capacity, high electrical output performance and good mechanical properties. These are likely due to: (1) the three-layer asymmetric fiber structure design of "moisture absorption-moisture removal-evaporation", which can utilize the capillary effect to absorb moisture on one side and effectively discharge moisture from the other side, ensuring continuous water flow through the negatively charged micro-nano channels in the fiber membrane, thereby solving the problem of unsustainable output in hydrovoltaic power generation; (2) the gradually increasing electronegative materials of "cellulose-polyacrylonitrile-polyvinylidene fluoride" promote charge separation and directional migration of ions, thereby maintaining the stability of the hydrovoltaic power generation system over a long period of time. Generate a stable high current output; (3) The hygroscopic layer is soaked in a hygroscopic salt solution, which has high hygroscopicity and provides positive and negative ions, thereby increasing the ion current density during directional water transport; (4) The thermal conductive filler added to the moisture-dissipating layer can provide a good thermal conductive path, which can effectively transfer heat from the hygroscopic layer to the evaporation layer, thereby increasing the water evaporation rate; (5) The layered filler added to the evaporation layer provides strength and barrier properties, thereby improving the mechanical and thermodynamic properties of the fiber membrane, including tensile strength, puncture resistance, and thermal deformation temperature; (6) The flow of water also drives the active metal electrode to undergo redox reactions to produce a large number of ions. The directional movement of these ions increases the ion current density, thereby generating sustainable high-performance output. Combining this fiber material with masks, clothing, etc. can not only meet the wearing comfort requirements, but also construct an energy collection system to directly power commercial electronic devices. The preparation method is simple and can be mass-produced.

[0076] The present invention provides a sustainable power generation fiber material based on a moisture absorption-evaporation cycle and a preparation method thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a sustainable power generation fiber material based on a moisture absorption-evaporation cycle, characterized in that: The following steps are involved: Step S1, preparing a hygroscopic layer: dissolving cellulose acetate in an organic solvent, preparing a cellulose microfiber membrane by electrospinning technology, then dissolving a hygroscopic salt in deionized water, soaking the cellulose microfiber membrane in the hygroscopic salt solution, placing it in a microwave reactor to in-situ grow hygroscopic salt ions, and preparing a hygroscopic layer after drying; Step S2, preparing a moisture-dissipating layer: dissolving polyacrylonitrile and a thermally conductive filler in an organic solvent, using the moisture-absorbing layer as a receiving substrate, and preparing a nanofiber moisture-dissipating layer by electrospinning technology; Step S3, preparing an evaporation layer: dissolving polyvinylidene fluoride and a layered filler in an organic solvent, and uniformly depositing nanofibers on the moisture removal layer by electrospinning technology to prepare an evaporation layer; Step S4, integration of power generation fiber materials: installing the active metal electrode on the hygroscopic layer, installing the graphite electrode on the evaporation layer, and integrating sustainable power generation fiber materials based on the hygroscopic-evaporation cycle.

2. The method according to claim 1, characterized in that In step S1, the organic solvent for dissolving cellulose acetate is at least one of acetone, dimethylformamide, and glacial acetic acid, and the concentration of cellulose in the solution is 0.2-30 wt%.

3. The method according to claim 2, characterized in that In step S1, when the cellulose micron fiber membrane is prepared by electrospinning technology, the electrospinning voltage is 15-45 kV, the spinning solution consumption rate is 0.5-12 mL / h, the receiving distance is 10-30 cm, and the average diameter of the obtained cellulose micron fiber is 0.5-6 μm, and the fiber membrane thickness is 5-200 μm.

4. The method according to claim 3, characterized in that In step S1, the hygroscopic salt is at least one of lithium chloride, calcium chloride, sodium chloride and potassium nitrate, the concentration of the hygroscopic salt in deionized water is 0.5-50wt%, the output power of the microwave reactor is 200-2000W, the reaction temperature is 30-100°C, and the reaction time is 1-60min.

5. The method according to claim 4, characterized in that In step S2, the organic solvent is at least one of dimethylformamide, dimethyl sulfoxide, sulfolane, and ethylene nitrate, and the concentration of polyacrylonitrile in the organic solvent is 0.2 to 30 wt %; The thermal conductive filler is at least one of aluminum oxide, zinc oxide, aluminum nitride, boron nitride, graphene, carbon nanotubes, silicon carbide, and silicon dioxide, and the concentration of the thermal conductive nano filler in the organic solvent is 0.5-50wt%.

6. The method according to claim 5, characterized in that In step S2, when the nanofiber dehumidification layer is prepared by electrospinning technology, the electrospinning voltage is 15-45 kV, the spinning solution consumption rate is 0.2-8 mL / h, the receiving distance is 10-30 cm, the average diameter of the obtained nanofibers is 50-800 nm, and the thickness of the dehumidification layer fiber membrane is 5-200 μm.

7. The method according to claim 6, characterized in that In step S3, the organic solvent is at least one of dimethylformamide, methyl vinyl ketone and dichloromethane, and the concentration of polyvinylidene fluoride in the organic solvent is 0.2-30 wt %; The layered filler is at least one of nano-mica flakes, natural montmorillonite, boron nitride and talcum powder, and the concentration of the layered filler in the organic solvent is 0.5-50wt%.

8. The method according to claim 7, characterized in that In step S3, in the process of uniformly depositing the nanofibers on the dehumidification layer by electrospinning technology, the electrospinning voltage is 15-45 kV, the spinning solution consumption rate is 0.1-5 mL / h, the receiving distance is 10-30 cm, the average diameter of the obtained nanofibers is 10-600 nm, and the thickness of the evaporation layer fiber membrane is 5-200 μm.

9. The method according to claim 8, characterized in that In step S4, the active metal electrode is at least one of aluminum, copper, iron, and silver, and the active metal electrode undergoes a redox reaction to provide a stable ion supply.

10. Sustainable power generation fiber material based on moisture absorption-evaporation cycle, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Micro-nano fiber membrane with efficient moisture absorption and cooling functions and preparation method of micro-nano fiber membrane

    CN110129994A

  • Moisture absorption and evaporation integrated power generation device based on cellulose and preparation method thereof

    CN115411971A

Cited By

  • Fluid power generation fiber with two-phase gradient structure, preparation method and application

    CN119932751A